Exploring Game-Based Inquiry Learning Application in a Maritime Science Museum: A Visitors’ Perspective - Sohaib Ahmed; Muhammad Zeeshan; David Parsons; Osama Rehman; Zeeshan Ahmed; Adnan Ahmad; Faizan Ahmad (Human Behavior and Emerging Technologies)
This article brings together the concepts of emerging technologies, game-based learning (GBL), and inquiry learning to conduct a research study undertaken in a maritime science museum. Over the last decade, the potential benefits of emerging technologies have enabled game-based inquiry activities in formal and informal pedagogical contexts. The use of ontologies has also grown significantly in representing learning content. In the science museum literature, there are a few applications found wherein ontologies are used for generating adaptive learning content. However, no study has been found in the literature that targets GBL for museum inquiry activities through emerging technologies using an ontology-driven approach. This paper outlines the results and analyses of research conducted on an ontology-driven GBL inquiry application, MUSEON. For evaluation purposes, the M3 evaluation framework was used and tested with 86 random visitors to explore visitors’ perspectives regarding the effectiveness of MUSEON. The results were encouraging as 71.6% of visitors were satisfied with their learning experiences in a game-based environment. Further, the experimental group performed well (74.6% score) in comparison with the control group (56.4% score) during inquiry learning activities about the maritime science museum exhibits.